Characterization of the palladium plasma produced by nanosecond pulsed 532 nm and 1064 nm wavelength lasers. (24th December 2021) - Asif, M; Amin, U; Rehman, Z U; Ali, R; Qayyum, H
Abstract: Palladium plasma produced by nanosecond pulsed 532 nm and 1064 nm wavelengths lasers is studied with the help of planer Langmuir probe. The experiment is conducted over a wide range of the laser fluence (1.6–40 J cm −2 ). The measured time of flight ions distributions are used to infer total charge, kinetic energy of the palladium ions and plasma parameters. Our results indicate that the ion charge produced by both laser wavelengths is an increasing function of the laser fluence. Initially, the ion charge produced by 1064 nm is lower than 532 nm, but it increases at much faster rate with the rise of laser fluence as the inverse bremsstrahlung plasma heating prevails at higher plasma densities. The most probable kinetic energy of the Pd ions produced by 1064 nm wavelength is also lower than that of 532 nm. The time varying plasma electron temperature and electron density are derived from the current–voltage plots of the two plasmas. For both wavelengths, the electron temperature and electron density rapidly climb to a maximum value and then gradually decline with time. However, in case of the 532 nm, the electron temperature and electron density remain consistently high throughout the laser plasma. The results are compared the available literature and discussed by considering surface reflectivity, ablation rate of the Pd target and laser plasma heating. The results presented in this work will provide more insight into the process of laser ablation and can be useful for the development of laser-plasma ion sources.